Syari’at Islam dan Hukum Nasional: Problematika Transformasi dan Integrasi Hukum Islam ke dalam Hukum Nasional - Nurrohman, Nurrohman (TAJDID, 2019)
Sharia law or Islamic law in Indonesia, recently, is undergoing the process of transformation and integration toward national law. During this process dualism in terms and institutions difficult to be avoided. If in education there are madrasah and school (sekolah), in law there are sharia law and national law. The question is whether, through gradual transformation, this dualism eventually heading to integration and unification of law? This paper will try to see the problems and handicaps faced by Indonesia in order to transform and integrate sharia law toward national law. But this paper will fistly discuss the relationship between Islamic law, human rights and international law, the position of Islamic law in national law system as well as how Islamic law interact with local culture. This research concludes that the transformation of Islamic law in Indonesia needs to consider the multi-ethnic, multi-cultural and multi-religious faction of Indonesia. Transformation must not only end in the formalization process but also the internalization process. If the internalization process goes well, then Islamic law will enter Muslim community awareness as ethical and moral awareness. So that at the private level Islamic law will be practiced, becoming a way of life regardless of whether it is formalized in legislation or not. For Islamic law to be formally transformed at the public level in legislation, Muslims need to renew their understanding of syûra and ijmâ.